Climate change : the fork at the end of now - Tomkiewicz, Micha (New York : Momentum Press, 2011)
People are currently paying much attention to the ability of present and future human populations to influence Earth's climate through the emission of greenhouse gases (GHGs) such as carbon dioxide. According to some, such a self-induced change in our physical environment qualifies humans for the distinction of a'superspecies' that has passed a threshold of biological evolution. Some 2 to 3 billion years ago, another organism changed the environment in a very pronounced way: a primitive unicellular organism called cyanobacteria (blue- green algae). These cyanobacteria'discovered' a new energy source that enabled them to develop a photosynthetic apparatus that assimilates carbon dioxide through conversion of solar energy to chemical energy. In the process, a'useless' waste product, oxygen, began to accumulate and gradually changed the composition of the atmosphere. As a result, new, more complex oxygen-consuming forms of life evolved, eventually leading to humans. The algae that started it all, while still flourishing, then became the first link in a very elaborate food chain.
List of illustrations -- Foreword -- Acknowledgments -- Preface -- About the author -- 1. Introduction -- 2. The issues -- 3. History -- 4. The carbon cycle -- 5. Energy, temperature, entropy, and light -- 6. The greenhouse effect -- 7. Sun, water, and weather -- 8. Modeling -- 9. Human involvement, the separation of variables, and the IPAT identity -- 10. Fossil fuels -- 11. Alternative energy sources -- 12. The economic balance -- 13. Politics: global issues, local decisions -- 14. What can I do, and what can I learn from doing it -- 15. Early signs -- 16. The future, the past, and the Just World Hypothesis -- Notes -- Appendix 1. Units conversions and equivalencies -- Appendix 2. The periodic table of elements -- Appendix 3. International treaties -- Further reading -- Index.
Includes index.
Keywords: Climatic changes; Global warming; Energy policy -- Social aspects